IMPLEMENTASI LEAN MANUFACTURING DALAM USAHA MIKRO DAN KECIL: STRATEGI MENINGKATKAN EFISIENSI OPERASIONAL - Nurul Aziz Pratiwi; Putri Mareta (Jurnal Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economic growth, but often face challenges in operational efficiency. This study aims to evaluate the effectiveness of the Lean Manufacturing training program for MSME owners in Bandung Regency. The methods used include material delivery, interactive discussions, and mentoring in waste identification. The evaluation results showed an increase in participant understanding from an average of 45% in the pre-test to 80% in the post-test, with a significant increase in understanding the concepts of waste elimination, Just-In-Time, and Kaizen. Despite the challenges in implementation, participants showed a commitment to implementing Lean principles gradually. Recommendations for further training and mentoring programs are proposed to support the sustainability of Lean Manufacturing implementation in MSMEs.